Uterine Adenosarcoma: A Retrospective 12-Year Single-Center Study - Yuan, Zhen; Yu, Mei; Shen, Keng; Yang, Jiaxin; Cao, Dongyan; Zhang, Ying; Zhou, Huimei; Wu, Huanwen (Frontiers in Oncology, 2019)
Objectives. The aim of the present study was to investigate the potential prognostic factors of uterine adenosarcoma. Methods. A total of 49 cases of uterine adenosarcoma were retrospectively reviewed at our institution between April 2006 and October 2018. Results. Median follow-up time was 34 months (range: 1-148). Median age was 47.50 years (19-75). Nineteen (38.78%) patients were uterine cervical adenosarcoma and 30 (61.22%) patients were uterine corpus adenosarcoma. Twenty-nine (59.18%) patients were polypoid with a stalk to the uterine cervix or corpus. Twenty-six (38.77%) patients were stage IA. Fifteen (30.61%) patients showed sarcomatous overgrowth. Six (12.24%) patients displayed lymphovascular space invasion (LVSI). Four (8.16%) patients had heterologous elements. In univariate analysis, Disease-free-survival (DFS) was associated with tumor location, presence of tumor stalk, heterologous elements, LVSI. In multivariate analysis, presence of tumor stalk remained an independently protective factor for recurrence (HR=0.088, P=0.005), and LVSI a risk factor for recurrence (HR=11.953, P=0.002). Fertility-sparing surgery (FSS) was performed in 7 stage IA patients. When patients of stage IA analyzed separately, FSS was not significant with the DFS or OS. Conclusions. Presence of tumor stalk remained an independently protective factor for recurrence. Along with adequate counseling, FSS may be acceptable in cases whose tumors present with stalks and without high risk factors.